Relationship of the gene pool of the Khants with the peoples of Western Siberia, Cis-Urals and the Altai-Sayan Region according to the data on the polymorphism of autosomic locus and the Y-chromosome - V. N. Kharkov; N. A. Kolesnikov; L. V. Valikhova; A. A. Zarubin; M. G. Svarovskaya; A. V. Marusin; I. Yu. Khitrinskaya; V. A. Stepanov (Вавиловский журнал генетики и селекции)
Khanty are indigenous Siberian people living on the territory of Western Siberia, mainly on the territory of the Khanty-Mansiysk and Yamalo-Nenets Autonomous Okrugs. The present study is aimed at a comprehensive analysis of the structure of the Khanty gene pool and their comparison with other populations of the indigenous population of Southern and Western Siberia. To address the issues of genetic proximity of the Khanty with other indigenous peoples, we performed genotyping of a wide genomic set of autosomal markers using high-density biochips, as well as an expanded set of SNP and STR markers of the Y-chromosome in various ethnic groups: Khakas, Tuvans, Southern Altaians, Siberian Tatars, Chulyms (Turkic language family) and Kets (Yeniseian language family). The structure of the gene pool of the Khanty and other West Siberian and South Siberian populations was studied using a genome-wide panel of autosomal single nucleotide polymorphic markers and Y-chromosome markers. The results of the analysis of autosomal SNPs frequencies by various methods, the similarities in the composition of the Y-chromosome haplogroups and YSTR haplotypes indicate that the Khanty gene pool is quite specific. When analyzing autosomal SNPs, the Ugrian genetic component completely dominates in both samples (up to 99–100 %). The samples of the Khanty showed the maximum match in IBD blocks with each other, with a sample of the Kets, Chulyms, Tuvans, Tomsk Tatars, Khakas, Kachins, and Southern Altaians. The degree of coincidence of IBD blocks between the Khanty, Kets, and Tomsk Tatars is consistent with the results of the distribution of allele frequencies and common genetic components in these populations. According to the composition of the Y-chromosome haplogroups, the two samples of the Khanty differ significantly from each other. A detailed phylogenetic analysis of various Y-chromosome haplogroups made it possible to describe and clarify the differences in the phylogeny and structure of individual ethnospecific sublines, to determine their relationship, traces of population expansion in the Khanty gene pool. Variants of different haplogroups of the Y-chromosome in the Khanty, Khakas and Tuvans go back to their common ancestral lines. The results of a comparative analysis of male samples indicate a close genetic relationship between the Khanty and Nenets, Komi, Udmurts and Kets. The specificity of haplotypes, the discovery of various terminal SNPs confirms that the Khanty did not come into contact with other ethnic groups for a long time, except for the Nenets, which included many Khanty clans.